The Effectiveness of Grammar Translation and Direct Method in Teaching English literature:A Quantitative Study of EFL Students at University of Benghazi (مجلة الفاروق للعلوم, 2026)
This study investigates the effectiveness of the Grammar Translation Method (GTM) and the Direct Method (DM) in teaching English literature from the perspectives of English as a Foreign Language (EFL) students at the University of Benghazi, Al-Abyar Branch. The study aims to identify students’ perceptions of these two pedagogical approaches and determine which method better supports comprehension, classroom engagement, and language development. A quantitative research design was employed using a structured questionnaire consisting of eight closed-ended items based on a four-point Likert scale. The questionnaire was administered to a purposive sample of 40 sixth-semester students enrolled in the English Department. The collected data were analyzed using descriptive statistics, including frequencies and percentages. The findings indicate that students generally recognized the instructional value of both teaching methods. The Grammar Translation Method was perceived as effective in facilitating the understanding of difficult literary concepts through the use of the learners’ first language and explicit grammar instruction. In contrast, the Direct Method received more favorable responses regarding students’ active participation, target-language use, visual support, and error correction techniques. Overall, the results suggest that while the Grammar Translation Method enhances comprehension of complex literary texts, the Direct Method provides a more interactive and communicative learning environment. The study concludes that combining the strengths of both methods may offer a more balanced and effective approach to teaching English literature in higher education. It recommends increasing the use of learner-centered instructional strategies, contextualized vocabulary teaching, visual aids, and communicative classroom activities to improve students’ engagement and academic achievement